Development of Problem Based Learning Collaborative (PBL-C) Physics E-Worksheet to Improve Student Problem Solving and Collaboration Skills - Tomi Putra Wijaya; Mundilarto; Insih Wilujeng (Jurnal Penelitian Pendidikan IPA, 2024)
Problem-solving skills are needed in the 21st century because, in life, humans will always be faced with problems. One way to solve the problem is through collaboration. This research was done with the purpose of improving students' problem-solving and collaboration skills through problem-based learning e-worksheets. This method in research was research and development through the model by ADDIE (analysis, design, development, implementation, and evaluation). The analysis carried out on development is one of validity and practicality. At the implementation stage, problem-based learning e-worksheets were tested in schools to determine the e-worksheets effectiveness. The design in research used was the one-group pretest-posttest design. The research results obtained were: 1) PBL-C physics e-worksheets that were developed fall into the category of valid and practical; 2) PBL-C physics e-worksheets are effective for use in learning to increase problem-solving skills and collaboration of students.